2017
DOI: 10.1101/134395
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of Membrane-tension Gated Ca Flux in Cell Mechanosensation

Abstract: Eukaryotic cells are sensitive to mechanical forces that they experience from the environment. The process of mechanosensation is complex, and involves elements such as the cytoskeleton and active contraction from myosin motors. Ultimately, mechanosensation is connected to changes in gene expression in the cell, or mechanotransduction.While the involvement of the cytoskeleton in mechanosensation is known, processes upstream to cytoskeletal changes is unclear. In this paper, using a microfluidic device that mec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Membrane tension affects cell migration (Gauthier et al, 2011; Houk et al, 2012; Keren et al, 2008; Mueller et al, 2017), vesicle fusion and recycling (Boulant et al, 2011; Gauthier et al, 2011; Maritzen and Haucke, 2017; Masters et al, 2013; Shillcock and Lipowsky, 2005; Shin et al, 2018; Thottacherry et al, 2017; Wen et al, 2016), the cell cycle (Stewart et al, 2011), cell signaling (Basu et al, 2016; Groves and Kuriyan, 2010; Houk et al, 2012; Huse, 2017; Romer et al, 2007), and mechanosensation (He et al, 2018; Phillips et al, 2009; Ranade et al, 2015). However, there has been controversy over the speed and degree to which localized changes in membrane tension propagate in cells (Diz-Muñoz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Membrane tension affects cell migration (Gauthier et al, 2011; Houk et al, 2012; Keren et al, 2008; Mueller et al, 2017), vesicle fusion and recycling (Boulant et al, 2011; Gauthier et al, 2011; Maritzen and Haucke, 2017; Masters et al, 2013; Shillcock and Lipowsky, 2005; Shin et al, 2018; Thottacherry et al, 2017; Wen et al, 2016), the cell cycle (Stewart et al, 2011), cell signaling (Basu et al, 2016; Groves and Kuriyan, 2010; Houk et al, 2012; Huse, 2017; Romer et al, 2007), and mechanosensation (He et al, 2018; Phillips et al, 2009; Ranade et al, 2015). However, there has been controversy over the speed and degree to which localized changes in membrane tension propagate in cells (Diz-Muñoz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As Rho GTPase activity drives actomyosin-mediated mechanical forces, mechanical forces also in turn modulate Rho GTPase activity via mechanotransduction: for example, mechanical compression of the cell membrane in human mesenchymal cells has been shown to reduce RhoA activity, mediated by mechanosensitive ion channels (14). Katsumi et al (15) show that the stretch of vascular smooth muscle cells inhibited Rac and decreased lamellipodia formation.…”
Section: Introductionmentioning
confidence: 99%
“…Actin dynamics and cortical contractile stress can also affect cell volume through multiple mechanisms such as vesicle transport and tension-activated channels [39,40]. In this paper we found that the actin cortex, on average, had a small effect on HN31 cell volume.…”
Section: Discussionmentioning
confidence: 64%